The Relationship Between Training Concentration With the Accuracy of Passing Futsal Club Bomber (FA) Jakarta - Syamsulrizal, Syamsulrizal; Iqbal, Muhammad (INSPIREE: Indonesian Sport Innovation Review, 2022)
The  purpose  of  the study. aiming to find out whether there is a relationship between the level of training concentration and the provision of futsal passing at the BOMBER FA club, Sawangan. Materials and methods. The method used in this study is the correlation method. The population in this study were the participants of the BOMBER FA futsal club, which amounted to 20 people. The sample is part or representative of the population under study. 3The sample in this study were participants of the BOMBER FA club, which amounted to 20 people. Results. According to the Product Moment correlation analysis, the value of rcount is 0.675 > rtable 0.532 and a significance value of 0.008 <0.05, which means "there is a relationship between the level of concentration (X) and the accuracy of futsal passing (Y).. Conclusions. Based on the results of the study, there is a positive and significant relationship between the Concentration Level and the Accuracy of Passing Futsal. Thus, the higher the concentration level, the higher the accuracy of futsal passing.